2011
DOI: 10.1002/ana.22223
|View full text |Cite
|
Sign up to set email alerts
|

Brain alkalosis causes birth asphyxia seizures, suggesting therapeutic strategy

Abstract: Our data indicate that brain alkalosis after recovery from birth asphyxia plays a key role in the triggering of seizures. We question the current practice of rapid restoration of normocapnia in the immediate postasphyxic period, and suggest a novel therapeutic strategy based on graded restoration of normocapnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 40 publications
(91 reference statements)
7
75
1
Order By: Relevance
“…The pronounced suppression of GDPs by a very small acid load (as seen with 1 mM propionate) indicates that neonatal neurons are exquisitely sensitive to changes in pH i . This finding is likely to have important implications on the generation of endogenous network events under physiological and pathophysiological conditions (Helmy et al, 2010) in the developing brain.…”
Section: Discussionmentioning
confidence: 83%
“…The pronounced suppression of GDPs by a very small acid load (as seen with 1 mM propionate) indicates that neonatal neurons are exquisitely sensitive to changes in pH i . This finding is likely to have important implications on the generation of endogenous network events under physiological and pathophysiological conditions (Helmy et al, 2010) in the developing brain.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study by Zhou et al (25) showed in an animal model that moderate hypercapnia may be protective following global cerebral ischemia. In addition, brain alkalosis has been shown to induce seizure activity in rodents after asphyxia (26). Ventilation strategies are of great relevance since a previous Finnish study showed a high prevalence of hypocapnia in patients treated with TH (27).…”
Section: Discussionmentioning
confidence: 99%
“…To mimic a persistent impaired gas exchange leading to hypoxia and hypercapnia, as seen during asphyxia, P6 pups of both genders randomly separated from 5 mothers from each dietary group (n = 28 pups/group) were exposed to a gas mixture of 9% O 2 and 20% CO 2 in N 2 for 90 min, as previously described [11], using a birth asphyxia model developed by Helmy et al [12]. All pups survived the exposure and were immediately returned to their mothers for 24-48 h. Two experimental groups resulted: PA group (PA-exposed pups whose mothers received standard diet) and HF-PA group (PA-exposed pups whose mothers received HFD).…”
Section: Animals and Experimental Conditionsmentioning
confidence: 99%